Organic Regime Promotes Evenness of Natural Enemies and Planthopper Control in Paddy Fields. Issue 2 (25th February 2019) - Yuan, Xin; Zhou, Wen-Wu; Jiang, Yan-Dong; Yu, Hang; Wu, Sheng-Yong; Gao, Yu-Lin; Cheng, Jia-an; Zhu, Zeng-Rong
Abstract: Planthoppers ( Nilaparvata lugens, Sogatella furcifera, and Laodelphax striatellus ) (Hemiptera: Delphacidae) are the most important pests affecting rice production. Pesticide spraying for its control may cause harmful effects on human health and the environment, especially the loss of biodiversity. The consequences of these changes on biodiversity and ecological services are well studied in tropical irrigated paddy fields, but are largely unknown in subtropical areas. Organic regime provides an environment-friendly method for biodiversity conservation; however, it is unclear whether this regime can suppress planthopper populations effectively in paddy fields. Consequently, we compared species richness, abundance, community structure, and evenness of natural enemies and planthoppers between organic and conventional rice fields ( n = 35) distributed across four sites in China. The results showed that species richness was higher in organic fields than in conventional fields. Shannon index and evenness of predators and parasitoids were higher in most of the organic fields than their conventional counterparts. Furthermore, planthopper density showed a significant negative relationship with increased richness and evenness for both predators and parasitoids. These results underscore the notion that management regimes influence biodiversity in rice field. Most importantly, this has direct implications on the efficacy of natural pest control services rendered by predators and parasitoids associated with planthoppers in China and potentially other rice production regions in Asia.